1983
DOI: 10.1038/306036a0
|View full text |Cite
|
Sign up to set email alerts
|

Optical recording of action potentials from vertebrate nerve terminals using potentiometric probes provides evidence for sodium and calcium components

Abstract: Optical methods are shown to monitor action potentials from a population of nerve terminals in the neurohypophysis of Xenopus. Calcium antagonists such as cadmium and nickel ions block a component of the action potential that probably reflects a calcium-mediated potassium conductance, and tetrodotoxin blocks an inward sodium current, revealing a calcium component to the action potential upstroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(118 citation statements)
references
References 31 publications
3
115
0
Order By: Relevance
“…Each slice was attached to the bottom of a plastic chamber with tungsten pins and maintained in Ringer's solution at 37°C. The sections were stained for 10 min with a voltagesensitive merocyanine-rhodanine dye, NK2761 (0.04% in Ringer's solution containing 1% DMSO; Hayashibara Biochemical Laboratories) (Kamino et al, 1981;Salzberg et al, 1983;Obaid et al, 1985). Thereafter, the excess dye was washed out with dye-free Ringer's solution for 90 min to allow the slice to recover.…”
Section: Methodsmentioning
confidence: 99%
“…Each slice was attached to the bottom of a plastic chamber with tungsten pins and maintained in Ringer's solution at 37°C. The sections were stained for 10 min with a voltagesensitive merocyanine-rhodanine dye, NK2761 (0.04% in Ringer's solution containing 1% DMSO; Hayashibara Biochemical Laboratories) (Kamino et al, 1981;Salzberg et al, 1983;Obaid et al, 1985). Thereafter, the excess dye was washed out with dye-free Ringer's solution for 90 min to allow the slice to recover.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the 45 phototoxicity of styryl dyes can be caused by singlet oxygen, an excited state of O 2 produced by energy transfer from the triplet state of the dye to molecular oxygen. 15,26 We investigated the singlet oxygen yields of the dyes by monitoring the emission from singlet oxygen at 1270 nm following excitation of FM4-64, 50 1b and 2b in air-saturated acetonitrile solutions. None of the dyes gave any significant signal at 1270 nm (compared to Rose Bengal, a standard singlet oxygen sensitiser, Φ = 0.74).…”
Section: In Vitro Cytotoxicitymentioning
confidence: 99%
“…Such a signal is usually not available. However, because dendritic processes have greater membrane area than cell somata, the voltage-sensitive dye fluorescence signal emphasizes corresponding dendritic activity (Salzberg, 1983;Salzberg et al, 1983;Grinvald et al, 1994) and that the CA1 apical dendrite is a key compartment for integration of excitatory synaptic inputs; therefore, to approximate the changes in fluorescence in these local dendritic compartments, we use patch recordings from the apical dendrite as a calibration signal. For all dendritic recordings, we plotted the change in voltage-sensitive dye fluorescence as a function of the change in membrane potential recorded from the dendrites.…”
Section: Ca1 Circuit Integration Of Afferent Inputsmentioning
confidence: 99%